Acceptance of a sensor-based online psychotherapy for adolescents with obsessive-compulsive disorder (SSTeP-KiZ) - Annika K Alt; Carolin S Klein; Anja Pascher; Annette Conzelmann; Franziska Kosel; Jan Kühnhausen; Karsten Hollmann; Tobias J Renner (Digital Health)
Background and aim E-mental health interventions with use of cognitive behavioral therapy methods and therapist contact via video have been well established in their effectiveness for various mental illnesses. With the help of sensors worn on the body, relevant contextual information can be made visible. In the SSTeP-KiZ study, the feasibility of a multimodal sensor system was tested, which was used in video-based psychotherapy for adolescents with obsessive-compulsive disorder during therapy sessions in the home environment. The present study investigated the acceptance and satisfaction of participating patients and families with the novel sensor-based therapy approach. Material and methods A mixed study design with focus groups was used. In a quantitative longitudinal study, personality characteristics of the study participants and families of the SSTeP-KiZ study were collected. Following the main study, a total of five focus group interviews were conducted with patients, parents, therapists to determine satisfaction and acceptance of the sensor technology. The study was part of the main SSTeP-KiZ study registered by ClinicalTrails.gov (NCT05291611) and used the COREQ-Checklist. Results The participants in the focus groups indicated a high level of satisfaction with the therapy method and would recommend the treatment to friends 100% of the time. One factor to be modified appears to be the personal contact design, particularly at the beginning of the therapy. Personality characteristics such as affinity for technology or acceptance of technology were not dependent on the patient's age or gender. Discussion The present results indicate that the sensor-based video therapy approach was accepted by patients and families and that the sensor system was experienced as practicable and supportive. To improve the use of sensor technology in psychotherapy further and to adapt the sensor system optimally to the needs of patients, further research involving users in the sense of participatory research is necessary. Clinical trial registration [ www.ClinicalTrials.gov ], identifier [NCT05291611]. The qualitative study is part of the SSTeP-KiZ main study.